Internacionalização e mobilidade acadêmica na Universidade Federal de São Carlos (UFSCar): análise da participação docente e discente nos programas da Associação de Universidades Grupo Montevidéu (AUGM) - Andrade, Bruno Soto de (Universidade Federal de São Carlos, 2025)
This study identifies, systematizes, and quantifies data on international academic mobility at the Federal University of São Carlos (UFSCar), with a particular focus on the programs of the Montevideo Group Association of Universities (AUGM), aiming to contribute to the development of institutional AUGM mobility indicators at UFSCar. Through a comprehensive literature review, the research seeks to analyze the internationalization process, the internationalization of science and technology, and the role of internationalization in higher education, especially regarding the academic mobility of undergraduate and graduate students, as well as faculty members. The methodological approach adopted is documentary, descriptive, quantitative and exploratory in nature, utilizing data from UFSCar’s Office for International Affairs. The objective is to collect, organize, and structure the data in alignment with the research objectives. The study maps variables such as participants' gender, age group, home and host institutions and countries, as well as financial support mechanisms. The findings indicate UFSCar’s active engagement in the AUGM ESCALA Programs. However, in the context of undergraduate mobility, the absence of systematized data impairs a comprehensive assessment of the outcomes and institutional impacts of both incoming and outgoing mobilities. Nonetheless, a significant reduction in the availability of places in the Undergraduate Student ESCALA Program suggests a potential correlation with changes in the funding structure for incoming mobilities. Regarding graduate-level mobility, the data suggest that the Graduate Student ESCALA Program was affected by the COVID-19 pandemic, yet the relatively low financial requirements point to the potential for expansion. In the ESCALA Faculty Program, the data reveal a higher number of incoming faculty to UFSCar compared to outgoing mobility. In terms of academic disciplines, a predominance of foreign students and faculty in the Exact Sciences is observed, whereas UFSCar students tend to seek mobility opportunities in the Humanities. The data also show a higher participation of female students in mobility activities at both undergraduate and graduate levels. Finally, the lack of data regarding race and ethnicity is noted, which constitutes a relevant gap, particularly within the context of Brazilian higher education institutions.
Internationalization and academic mobility at the Federal University of São Carlos (UFSCar): analysis of faculty and student participation in the Montevideo Group Association of Universities (AUGM) programs
Keywords: Internacionalização da educação superior; Mobilidade acadêmica internacional; Sul global; Internationalization of higher education; International academic mobility; Global south; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL; OUTROS::RELACOES INTERNACIONAIS